A study of pathogenesis of Acanthosis nigricans and its clinical implications - Neerja Puri (Wolters Kluwer Medknow Publications, 2011)
Background: Acanthosis nigricans (AN) is a dermatosis characterized by thickened, hyperpigmented plaques, typically on the intertriginous surfaces and neck. Common in some populations, its prevalence depends on race. Clinicians should recognize AN; it heralds disorders ranging from endocrinologic disturbances to malignancy. In this review, we discuss the pathogenesis of AN and its clinical implications and management. Materials and Methods: We selected 30 patients for the study. Diagnosis of associated disorders was established by history, physical examination, body mass index (BMI), hormone measurements by radioimmunoassays of thyroidnfunction tests, free testosterone, 17 (OH) progesterone, dehydroepiandrosterone sulfate (DHEAS), cortisol, gonadotropins, prolactin, immunoreactive insulin, and C-peptide levels. Results and Discussion: In our study, the flexural involvement (flexures of groins, knees and elbows) was seen in 40% patients, lip involvement was seen in 6.6% patients, and dorsal involvement was seen in 3.3% patients each. Increased serum testosterone levels were seen in 13.3% patients and increased DHEAS levels were seen in 20% patients. Regarding the types of AN, obesity induced AN or pseudo-AN was seen 70% patients, syndromic AN was seen in 23.35% patients and malignant AN was seen in 6.6% patients. The commonest histopathological feature of patients with AN was hyperkeratosis, seen in 100% patients, papillomatosis was seen in 90% patients, dermal infiltrate of lymphocytes and plasma cells was seen in 60% patients, horn pseudocysts were seen in 30% patients, and irregular acanthosis was seen in 26.6% patients.